Transgenerational Epigenetics: The Role of Maternal Effects in Cardiovascular Development - Ho, Dao H. (Oxford University Press, 2014)
Transgenerational epigenetics, the study of non-genetic transfer of information from one generation to the next, has gained much attention in the past few decades due to the fact that, in many instances, epigenetic processes outweigh direct genetic processes in the manifestation of aberrant phenotypes across several generations. Maternal effects, or the influences of maternal environment, phenotype, and/or genotype on offsprings’ phenotypes, independently of the offsprings’ genotypes, are a subcategory of transgenerational epigenetics. Due to the intimate role of the mother during early development in animals, there is much interest in investigating the means by which maternal effects can shape the individual. Maternal effects are responsible for cellular organization, determination of the body axis, initiation and maturation of organ systems, and physiological performance of a wide variety of species and biological systems. The cardiovascular system is the first to become functional and can significantly influence the development of other organ systems. Thus, it is important to elucidate the role of maternal effects in cardiovascular development, and to understand its impact on adult cardiovascular health. Topics to be addressed include: (1) how and when do maternal effects change the developmental trajectory of the cardiovascular system to permanently alter the adult’s cardiovascular phenotype, (2) what molecular mechanisms have been associated with maternally induced cardiovascular phenotypes, and (3) what are the evolutionary implications of maternally mediated changes in cardiovascular phenotype?